Representasi Budaya Jepang dalam Ryokan pada Anime Hanasaku Iroha - San, San; Ari Sulatri, Ni Luh Putu; Luhur Wedayanti, Ni Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 2 (2023), 2023)
This research is titled "Representation of Japanese Culture on Ryokan in the Hanasaku Iroha Anime". This study aims to determine the characteristics of the ryokan depicted in the Hanasaku Iroha anime and the representation of Japanese culture in the ryokan. The data was collected using the observation method, analyzing the data using the descriptive method, and presenting the data analysis using the informal method. The theory used is the Theory of Anthropology and the Semiotic Theory of Roland Barthes. Based on the research results, it is known that the depiction of the ryokan in the Hanasaku Iroha anime is divided into the location of the ryokan and the food facilities in the ryokan. Most of the ryokan are built near the onsen with the aim of allowing guests to enjoy the onsen with the natural heat of the mountains, but it is possible that ryokan are also built in urban areas. The food facilities in the ryokan are kaiseki ryori as Japanese specialties which are one of the attractions for guests to stay. In the cultural representation of the ryokan, there are three cultural concepts found in the data. The first is the concept of uchi-soto which is seen from the genkan area with guests as soto and staff as uchi so that when entering the ryokan, guests have entered the uchi area of ??the ryokan. Second, the representation of the wabi-sabi concept can be seen from the ryokan garden focuses on imperfection and simplicity. Finally, the embodiment of the wa and ma concepts is depicted from the washitsu room which emphasizes harmony and empty space.